Enhancing Performance of Distributed Transactions in Microservices via Buffered Serialization - Munonye, Kindson; Martinek, P. (Journal of Web Engineering, 2020)
Although the Microservices Architecture comes with a number of benefits, it is a challenge to design an efficient transaction management for multi-agent transactions that span across multiple services. Since microservices design require a loose coupling between service logic and resources, data used by a distributed transaction is spread across different nodes, there is need to an effective way to ensure data portability, speed consistency for transaction in microservices. Therefore this research addresses both the issue of improving transaction performance and maintaining data portability for distributed transactions in microservices. A novel approach to transaction management termed ‘buffered serialization’ is proposed in this research as a way to improve transaction management by the use serialization libraries. This work has a three-part objective which are (1) to highlight the challenges of distributed transaction management in microservices, (2) to propose an enhanced approach to transaction management through the use of buffered serialization between services (3) to provide a proof of concept for this novel approach. Obtained result indicate a 60% improvement in transaction failure recovery time, 10% higher success rate for load tests but an insignificantly higher resource utilization values.